Body Exercise Techniques for Blind Children : A New Design of Basic Balinese Dancing Techniques for Special Categories - Ni Wayan Mudiasih; Tudhy Putri Apyutea Kandiraras; Ni Made Pande Suari (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The purpose of this study was to find a new design for basic Balinese dance techniques for blind children. So far, the basic techniques of Balinese dance are difficult for blind children to learn. In this regard, a new design for the basic technique of Balinese dance has emerged for beginners in a special category. The problems are: 1) how to form a new draught of basic Balinese dance techniques for blind children?; 2) what are the benefits of the new design of basic Balinese dance techniques in a special category for blind children?. This new design of basic Balinese dance techniques for blind children was researched using the R&D method. All data was obtained through field studies and literature studies on blind children. All data were analysed qualitatively using aesthetic theory and deconstruction theory from the perspective of art studies. The design of basic Balinese dance techniques for beginners for this special category was constructed after basic research was completed with the help of deconstruction theory. The results of the study show that : 1) the new design of the basic techniques of Balinese dancing for beginners is a body exercise technique for blind children; and 2) the benefits of the new design of the basic Balinese dancing techniques can train breathing, balance, and flexibility of joint muscles to strengthen stamina, memory, and movement power of blind children in Balinese dancing.